2018
DOI: 10.1007/s13762-018-1937-y
|View full text |Cite
|
Sign up to set email alerts
|

Eco-innovation in garden irrigation tools and carbon footprint assessment

Abstract: This article describes the eco-innovative characteristics implemented in electronic devices for irrigation with smart-gardening solutions, such as internet connection for weather forecast and sensors of soil moisture contents, as well as a database with different plants necessities. The main function of these products is to collect and analyse the information related to plants needs, thus reducing water and fertiliser consumption. In addition to quantify the environmental impact of savings in these two resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Such systems have proven to have decreased the amount of water used, provided a uniform water distribution and have decrease the amount of fertilizer needed. This correlates directly with the reduction of operational costs on the long run while covering gradually for the capital costs initially invested [17][18].…”
Section: Resultsmentioning
confidence: 97%
“…Such systems have proven to have decreased the amount of water used, provided a uniform water distribution and have decrease the amount of fertilizer needed. This correlates directly with the reduction of operational costs on the long run while covering gradually for the capital costs initially invested [17][18].…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have investigated the potential for IoT to reduce environmental impacts in the use-phase of products (e.g., [20,21]). In this study, we add to this by showing that IoT can also bring significant impact reductions in the production phase since it can enable both product lifetime extension and increased product recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they noted that the use-phase impact reduction depended strongly on the ability of the 'smart system' to steer user behavior in a more sustainable direction, mainly to reduce food waste. Yuli et al [21] studied the net GWP reduction from an IoT-enabled irrigation system compared to a conventional irrigation system and concluded that the savings outweighed the impacts. The savings were estimated by the potential for the IoT solution to reduce water and fertilizer consumption in the irrigation system's use phase, while added impacts from the IoT solution itself (sensors, control unit, and gateway) were analyzed cradle-to-grave.…”
Section: Introductionmentioning
confidence: 99%
“…For many other assessments network infrastructure is not included at the point of intervention and is thus not included in the analysis. For example, Yuli et al (2019) provide a detailed description of the communication devices involved in a precision irrigation control system including sensors and controllers installed in the field, a router housed nearby, and the online systems that include data storage in the 'cloud' and a user interface and store. These online systems are, however, not included in their detailed LCA.…”
Section: Network Infrastructurementioning
confidence: 99%